Available Pharmacological Methods of Obesity Treatment Worldwide - Drugs Review - Zielińska , Weronika; Wanat, Joanna; Dzikowska, Izabela; Siejka, Agata; Stefaniak, Daria; Warunek, Aleksandra; Gronowicz, Gabriela; Homa, Wojciech; Chról, Michał (Quality in Sport, 2025)
Introduction and Purpose: The prevalence of obesity is increasing year by year all over the world. Along with the progression of the disease, there is also progress in the pharmacotherapy of obesity. The developing epidemic of obesity indicates that non-pharmacological methods are not able to solve this problem. For over 60 years, there has been a search for the ideal drug that would allow not only weight loss but also maintaining a lower bodyweight and reducing the cardiovascular risk that obesity carries. It is very important to thoroughly examine the intricacies and impact of the drugs used in order to properly select the drug for each case individually, depending on the source of obesity. The aim of this review is to present the available drugs together with the mechanism of their actions and the side effects associated with their use. Brief Description of the State of Knowledge: There are currently 7 drugs approved by the Food and Drug Administration (FDA) and 6 approved by the European Medicines Agency (EMA) for long-term (over 12 weeks) treatment of obesity. All available drugs are prescribed for patients with a body mass index of≥ 30 kg/m2 or ≥ 27 kg/m2 with concomitant comorbidity. However, their use should be combined with intervention in the lifestyle of the patients. Summary: Obesity affects a large part of society and the number of patients is still growing. This global problem is a therapeutic challenge for doctors. A properly selected drug for the patient's needs may prove to be crucial in the treatment of obesity. Materials and Methods: The literature review was conducted using the Google Scholar database